L-arginine improves uterine spiral arterial wall thickness in mouse models of preeclampsia - Soetrisno, Soetrisno; Sulistyowati, Sri; Wibowo, Anwar Sandi (Universa Medicina, 2017)
BackgroundPreeclampsia is a major cause of maternal and fetal morbidity and mortality. The imbalance of anti-angiogenic and angiogenic factors plays a role in endothelial dysfunction in preeclampsia. L-arginine is expected to improve the process of spiral artery remodeling. This study aims to examine the use of L-arginine to repair endothelial damage by measuring the thickness of uterine spiral arteries in mouse (Mus musculus) models of preeclampsia.MethodsThe researchers carried out an experimental study using 30 sixteen-day old pregnant Swiss mice (in good health, weighing 20-25 grams), which were randomly divided into 3 groups (each consisting of 10 mice). The groups were as follows: 1) normal pregnancy K(-); 2) preeclampsia model K(+); and 3) preeclampsia model receiving L-arginine (P). The authors performed histopathological examination of the mouse placenta, which had been dissected, embedded in paraffin wax and subsequently stained with hematoxylin and eosin (HE). The results were analyzed in SPSS v. 21 for Windows using Anova with Tukey.ResultsThe mean thickness of spiral arteries in group K(-) was 53.95 + 26.96 mm, in K(+) 96.50 + 16.66 mm, and in P 62.79 + 8.04 mm. Statistically, there were significant differences between groups K(-) and K(+) (p=0.001) and between K(+) and P (p=0.000), but non-significant differences between K(-) and P (p=1.000).ConclusionsThe treatment with L-arginine proved to be effective in repairing endothelial damage by reducing intimal hyperplasia and atherosis and, in turn, the thickness of uterine spiral arteries in mouse models of preeclampsia.